Tradições culturais no ensino de música em classes hospitalares (Revista NUPEART, 2021)
This article aims to describe music teaching practices in hospital classes based on a proposal that was grounded on musical knowledge from the oral tradition of Northeast of Brazil. When considering the specificities of schooling in a hospital environment, a music teaching project was developed that integrated knowledge from the students' experiences associated with the knowledge defined in the school curriculum. From the experience developed, there was an intense participation of children in music classes, the results of which demonstrate the importance of manifestations of popular culture, especially cultural traditions, for the teaching and learning processes at school. Reflections on teaching practice unfold in suggestions for the formation of future professionals who are interested in working in this educational modality.
Keywords: Music teaching. Hospital Class. Cultural Traditions